The afterlife of holocaust memory in contemporary literature and culture - Crownshaw, Richard 1970- (Palgrave Macmillan memory studies, 2010)
"This bold intervention into the debate over the memory and post-memory of the Holocaust both scrutinises recent academic theories of post-Holocaust trauma and provides a new reading of literary and architectural memory texts related to the Holocaust"--